Penutian materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Bloomfield, Leonard, 1887-1949; Francescato, Giuseppe; Swadesh, Morris, 1909-1967 (1952)
Several items relating to the Penutian language family have been identified in the C. F. Voegelin Papers. Of particular interest is Subseries VI. Penutian, including Mayan and Zoque, of Subcollection II, Series II. Research Notes. The contents of this subseries includes folders of materials under the following headings: Chinookan-Chinook, Wishram, Kathlamet; Klamath-Modoc; Maidu; Maya (Tzeltal); Miwok; Penutian; Sahaptin; Takelma; Tsimshian; Yokuts; and Zuni. There are also Penutian materials in Subcollection II, Series IV. Works by Others. These include Leonard Bloomfield's "Penutian" sketch; Giuseppe Francescato's masters thesis, "A Structural Comparison of the Californian Penutian" (1952); and Morris Swadesh's "Problems of Long-Range Comparison in Penutian." Researchers should also view the individual entries for distinct Penutian languages.